Exploratory comparative transcriptomic analysis reveals potential gene targets associated with Cry1A.105 and Cry2Ab2 resistance in fall armyworm (Spodoptera frugiperda) - Castellane, Tereza Cristina L. [UNESP]; Fernandes, Camila C.; Pinheiro, Daniel G. [UNESP]; Lemos, Manoel Victor Franco [UNESP]; Varani, Alessandro M. [UNESP] (Springer Nature, 2024)
Genetically modified (GM) crops, expressing Bacillus thuringiensis (Bt) insecticidal toxins, have substantially transformed agriculture. Despite rapid adoption, their environmental and economic benefits face scrutiny due to unsustainable agricultural practices and the emergence of resistant pests like Spodoptera frugiperda, known as the fall armyworm (FAW). FAW’s adaptation to Bt technology in corn and cotton compromises the long-term efficacy of Bt crops. To advance the understanding of the genetic foundations of resistance mechanisms, we conducted an exploratory comparative transcriptomic analysis of two divergent FAW populations. One population exhibited practical resistance to the Bt insecticidal proteins Cry1A.105 and Cry2Ab2, expressed in the genetically engineered MON-89Ø34 − 3 maize, while the other population remained susceptible to these proteins. Differential expression analysis supported that Cry1A.105 and Cry2Ab2 significantly affect the FAW physiology. A total of 247 and 254 differentially expressed genes were identified in the Cry-resistant and susceptible populations, respectively. By integrating our findings with established literature and databases, we underscored 53 gene targets potentially involved in FAW’s resistance to Cry1A.105 and Cry2Ab2. In particular, we considered and discussed the potential roles of the differentially expressed genes encoding ABC transporters, G protein-coupled receptors, the P450 enzymatic system, and other Bt-related detoxification genes. Based on these findings, we emphasize the importance of exploratory transcriptomic analyses to uncover potential gene targets involved with Bt insecticidal proteins resistance, and to support the advantages of GM crops in the face of emerging challenges.
Keywords: Brazilian corn field; Crystal proteins; Phase I detoxification enzymes; Phase II metabolism enzymes; Phase III transporters; Plant-pest interactions